Analyzing One Health governance and implementation challenges in Mexico - Jennifer Hegewisch-Taylor; Anahí Dreser; Alondra Coral Aragón-Gama; María Antonieta Moreno-Reynosa; Celso Ramos Garcia; Arne Ruckert; Ronald Labonté (Taylor & Francis Group, 2024)
Establishing a robust One Health (OH) governance is essential for ensuring effective coordination and collaboration among human, animal, and environmental health sectors to prevent and address complex health challenges like zoonoses or antimicrobial resistance. This study conducted a mixed-methods environmental scan to assess to what extent Mexico displays a OH governance and identify opportunities for improvement. Through documentary analysis, the study mapped OH national-level governance elements: infrastructure, multi-level regulations, leadership, multi-coordination mechanisms (MCMs), and financial and OH-trained human resources. Key informant interviews provided insights into enablers, barriers, and recommendations to enhance a OH governance. Findings reveal that Mexico has sector-specific governance elements: institutions, surveillance systems and laboratories, laws, and policies. However, the absence of a OH governmental body poses a challenge. Identified barriers include implementation challenges, non-harmonised legal frameworks, and limited intersectoral information exchange. Enablers include formal and ad hoc MCMs, OH-oriented policies, and educational initiatives. Like other middle-income countries in the region, institutionalising a OH governance in Mexico, may require a OH-specific framework and governing body, infrastructure rearrangements, and policy harmonisation. Strengthening coordination mechanisms, training OH professionals, and ensuring data-sharing surveillance systems are essential steps toward successful implementation, with adequate funding being a relevant factor.